Optimization of Banana Peel Waste as A Raw Material for Making Environmentally Friendly Bioplastic - Apriyanto, Apriyanto; Hidayat, Surya; Aslam, Bilal (Journal Ligundi of Community Service, 2025)
Background. Plastic pollution has become a critical global environmental issue due to the non-biodegradable nature of conventional plastics derived from petrochemicals. In response to the growing demand for sustainable alternatives, researchers have turned to organic waste materials as potential bioplastic feedstock. Banana peel, a commonly discarded agricultural byproduct, contains high levels of starch and cellulose, making it a promising raw material for biodegradable plastic production. Purpose. This study aims to optimize the use of banana peel waste in the formulation of environmentally friendly bioplastics. Method. The research employed an experimental method with a quantitative approach, utilizing variations in plasticizer concentrations (glycerol) and drying temperatures to identify optimal conditions for bioplastic synthesis. The banana peels were processed through washing, boiling, blending, and filtration before being mixed with plasticizers and molded into sheets. Mechanical properties such as tensile strength, flexibility, and biodegradability were evaluated according to ASTM standards. Results. The results indicated that a glycerol concentration of 30% and a drying temperature of 80°C yielded the most favorable bioplastic properties. The optimized bioplastic demonstrated high biodegradability within 21 days and sufficient tensile strength for lightweight packaging applications. The findings support the feasibility of banana peel-based bioplastics as an eco-friendly alternative to synthetic plastics. Conclusion. This study concludes that banana peel waste can be effectively utilized as a sustainable biopolymer source, contributing to both waste reduction and the development of green materials. Further research is recommended to enhance durability and scalability for industrial use.